Representasi Gaya Hidup Studi di Luar Negeri Dalam Unggahan Instagram Influencer Gitasav (The Commercium, 2021)
Instagram allows users to share photos and videos on their daily activities through their lifestyle. Users that have the freedom to share photos and videos, lead those creative individuals to make the content enticing and invite other users to be interested in visiting their page. From here comes the term of celebgram or influencer, they have thousands and even millions of followers and makes an individual with their uniqueness as a role model to be followed in their daily activities. The researcher is interested in describing how the educational lifestyle is displayed in posts on Instagram as a social media, taking the research titled as "Presentment of the Study Abroad Lifestyle from @Gitasav as an Influencer in Her Instagram posts”. This type of research is a qualitative research using Roland Barthes Semiotics analysis that is looking for the meaning of denotation, connotation, and myth of each picture. The results of the research are the lifestyle of studying abroad which is adopted by the researcher including the lifestyle in learning, the lifestyle in activism, the lifestyle in making friends, the lifestyle of International Volunteer Tourism. Gitasav is one of the Indonesian Influencers with quite a lot of followers. Using his Instagram social media to share his daily moments to the demands of content. In the upload to the @Gitasav account, it shows that the educational lifestyle shown causes the sweet dreams of studying abroad to be achieved by everyone. Then creating social inequality that occurs, the higher the standardization in the mindset of the Indonesian people that a good education can only be obtained if studying abroad.